Efecto de la gamificación como estrategia para la educación híbrida en estudiantes universitarios - Morón Hernández, Julia Liliana (2022)
Objective. Determine the effect of gamifcation as a strategy for hybrid education in university students. Methods. A quantitative approach, pre-experimental design and applied research were used. The sample consisted of 20 students from the professional academic school of Language and Literature of the Universidad Nacional San Luis Gonzaga of Ica. Information was compiled using a survey. A 24-question Likert-type questionnaire was elaborated. In the theoretical basis for the application of hybrid education, the contributions of the Universidad Politécnica of Madrid were considered. Hypothesis inference was made using the Wilcoxon T statistic. Results. A p-value < 0.00 was obtained; therefore, the alternate hypothesis is accepted and the null hypothesis is rejected. Conclusions. The study concludes that the signifcance level is statistically signifcant.